EDUCATIONAL TRANSFORMATION: THE EFFECTIVENESS OF EDUCATIONAL MANAGEMENT IN THE ERA OF INDEPENDENT LEARNING - Mohamad Kamil Salas (Adisam Publisher, 2024)
The way that education is changing in the age of self-directed learning emphasizes the importance of adapting to technological developments, encouraging creativity and innovation, the very important role of teachers, and technology's application in education. the shift in education that led to the Merdeka era's successful educational management. The way that education is changing towards the effectiveness of educational management in the era of independent learning involves several key aspects that need to be considered, namely curriculum flexibility, technology and access to information, competency-based learning, collaboration and partnerships, performance-based assessment, teacher empowerment and principals, efficient resource management, and inclusion and diversity. The effectiveness of educational management also plays a role in optimizing the use of human resources, directing goals, and overcoming challenges that arise in the world of education. Education continues to develop from time to time, and education management has plays a crucial part in overseeing, controlling, and raising the standard of instruction in a variety of educational settings. A review of the literature was the research method employed in this paper. This research discusses the management of learning methods and curriculum in the independent learning era, human resource management in the independent learning era, and strategic plan management in the independent learning era.